2016
DOI: 10.1039/c6cc05947c
|View full text |Cite
|
Sign up to set email alerts
|

Chiral carbon dots derived from guanosine 5′-monophosphate form supramolecular hydrogels

Abstract: Guanosine 5'-monophosphate, (5'-GMP), is a self-assembling natural nucleotide that has unique potential to form ordered supramolecular structures. We herein describe an intriguing property of Na2(5'-GMP) to form blue emitting chiral carbon dots (G-dots) that exhibit excitation dependent down-conversion and up-conversion fluorescence signature and self-assemble to form fluorescent hydrogels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 62 publications
0
60
0
Order By: Relevance
“…Moving beyond ion transportation, Gquartet struc tures have also been exploited for the construction of functional nanostructures. For instance, Dash and col leagues exposed GMP to microwaveassisted thermal treatment in order to assemble carbon dots 68 . While GMP itself does not possess interesting spectroscopic properties, these socalled Gdots were found to have interesting fluorescence upconversion properties and can be readily converted in fluorescent Gdot hydrogels in the presence of K + , which were shown to have high ther mal stability (gel-sol transition temperature >70 °C) and elasticity.…”
Section: Wwwnaturecom/natrevchemmentioning
confidence: 99%
“…Moving beyond ion transportation, Gquartet struc tures have also been exploited for the construction of functional nanostructures. For instance, Dash and col leagues exposed GMP to microwaveassisted thermal treatment in order to assemble carbon dots 68 . While GMP itself does not possess interesting spectroscopic properties, these socalled Gdots were found to have interesting fluorescence upconversion properties and can be readily converted in fluorescent Gdot hydrogels in the presence of K + , which were shown to have high ther mal stability (gel-sol transition temperature >70 °C) and elasticity.…”
Section: Wwwnaturecom/natrevchemmentioning
confidence: 99%
“…The observed optical properties are in accordance with other cysteine based chiral CDs, prepared using hydrothermal synthesis. [33][34][35][36][37][38] The prominent peaks of the previously reported hydrothermal cysteine-based CDs were also centred around $250 nm and $350 nm. The similarities in optical properties of CDs from the two different synthesis methods can be attributed to the use of the same precursors with similar resulting functional groups and properties.…”
Section: Resultsmentioning
confidence: 66%
“…One of the rst chiral CDs reported in the literature was synthesized by Ghosh et al from the nucleotide guanosine 5 0 -monophosphate, where these G-dots were capable of intrinsically self-assembling to form biodegradable chiral hydrogels which could be used for biomedical applications and drug delivery. 33 Zhang et al also synthesized chiral CDs through hydrothermal synthesis by using L-and D-cysteine with citric acid. These CDs were explored as electrochemical probes for enantioselective recognition towards small target molecules such as enantiomeric tartaric acid, through a combination of electrochemical impedance spectroscopy (EIS) and linear sweep voltammetry.…”
Section: Introductionmentioning
confidence: 99%
“…The abundant and flexible modes of interaction is the key of nanoparticle formation. As a matter of fact, it has been reported that, aggregation of self‐H‐bonding guanosine monophosphate can be the precursor to highly fluorescent carbon dots …”
Section: Porous Materials Based On Nucleobase H‐bonding or Metal Coormentioning
confidence: 99%